A Comprehensive Review of the Marketed Antiulcer Polyherbal Formulations: Pharmaceutical Science-Pharmacology & Toxicology - Gupta, Manish Kumar; Khade, Medha Amol; Srivastava, Birendra; Hyam, Supriya Rajesh; Khade, Amol Baban (International Journal of Life Science and Pharma Research, 2022)
An imbalance in the aggressive factors and protective factors in the gastrointestinal tract leads to peptic ulcers. Modern medicinal prescriptions for ulcers involve the use of allopathic drugs. However, several disadvantages, such as side effects, discordancy, and altered physiological aspects, have led to the quest for alternative safer medications. The use of herbs to treat ulcers has been practiced for decades in Ayurveda. A combination of such herbs, known as polyherbal formulation, shows several advantages like synergistically augmented beneficial effects, better patient compliance, and reduction in dose of individual drugs without compromising the therapeutic effects. In recent years, this valuable traditional knowledge of the medicinal values of herbs, along with current value-added developments, has ensured the usage of improved Ayurvedic medicine in a milieu of treatments. In the last two decades, many polyherbal formulations have been developed and evaluated for their antiulcer potential. The advancements in analytical methods have even led to the isolation of the phytoconstituents from crude herbal drugs, and their benefits in therapeutics have been studied. The core aim of the current review is to enlighten the comprehensive overview of the composition of some marketed antiulcer polyherbal formulations and the preclinical models to prove their gastroprotective potentials based on scientific findings.